REMOVABLE NOUNS OF «COMMON GENDER»: PROBLEMATIC ASPECTS - Dzhochka, Iryna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The purpose of the study is to identify and analyze the factors and means of expressing the grammatical meaning of gender in inflected nouns - grammatical homonyms, which, depending on the context, can nominate persons or creatures of both sexes.. Research methodology. In order to systematize the material, to reveal the factors and methods of differentiation of grammatical gender meanings in the nouns of the "common gender", the descriptive (with the techniques of component and contextual analysis) was used. The comparative and typological analysis was also used to clarify the lexical-semantic, morphological, word-formation, and syntactic means that influence the gender of a certain grammatical form of a noun. The results of the study. It has been established that the mutable nouns of the "common gender" are the names of persons (rarely animals), representing the semantic and grammatical manifestation of the category of gender. They do not form a separate gramma of the genus but are grammatical homonymous forms that, depending on the context, can nominate persons of both sexes or distinguish males or females within faunonyms. The majority of mutable nouns of the "common gender" belong to feminines (homonymous forms marked with grammatical feminine gender), among which both stylistically neutral and expressively colored lexemes have been attested. Masculinities (homonymous forms marked with grammatical masculine gender) constitute the periphery of the group of "common gender" nouns, since, given the current trends in the gender categorization of nouns, they lose the status of homonymous forms, forming correlative pairs with feminine derivatives, the components of which differ only in the grammatical meaning of gender. In modern linguo-Ukrainian studies, they are defined as "paired gender" nouns. Practical significance. The article analyzes in detail those noun forms that have different interpretations in different lexicographic sources. The author points to the adjacent groups of nouns that represent the phenomenon of semantic and grammatical asymmetry of genitive forms that do not belong to the "paired" nouns. The change in the status of masculinities in the modern Ukrainian language is substantiated.